PENERAPAN PEMASARAN VIRAL PADA UKM RUMAH BATIK TULIS MADURA - Indah Purnama Sari (Sosio e-Kons, 2016)
Advances in technology are so rapid has been giving a new color to the business world. Companies are encouraged to do the practice of marketing and new business, which is Internet-based (viral marketing). This article is to describe the application of viral marketing at Small and Medium Enterprises (UKM) Rumah Batik Tulis Madura experiencing constraints are still scale local marketing. Application of viral marketing that has been done on UKM Rumah Batik Tulis Madura via e-mail, social networking site, and e-commerce in the form of an online store (website). The philosophy of viral marketing such as viruses (in terms of speed of deployment) allows the dissemination of information (promotion) is also rapid and massive that deserve to be alternative solutions to market batik can reach an even broader global. The constraints faced in the management of e-commerce online stores can be resolved by working with the developer website. This study can be a a reference by the wider community, including UKM, in the development of the marketing system. Keywords: viral marketing, UKM